2021
DOI: 10.1159/000517357
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Single- and Double-Injection Technique for Ultrasound-Guided Supraclavicular Block: A Randomized Controlled Study

Abstract: <b><i>Background:</i></b> The supraclavicular approach to brachial plexus block is a commonly employed regional anesthesia technique for providing surgical anesthesia and postoperative analgesia for patients undergoing upper limb fractures. With ultrasound (US) guidance, the success rate of the block is increased, and complications like pneumothorax and vascular puncture are minimized. The block can be performed using single injection at the corner pocket or double injection, that is, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Another interesting observation was that the majority of the patients reported anesthesia in the territory of the intercostobrachial nerve too. In contrast to our study, Vallapureddy et al [ 9 ] found that sensory and motor blockades of the musculocutaneous, median, radial, and ulnar nerve distribution were similar in both groups. Choi et al [ 10 ] and Arab et al [ 11 ] found that the rate of blockage of nerves was lower in the single-point injection group, which is similar to our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Another interesting observation was that the majority of the patients reported anesthesia in the territory of the intercostobrachial nerve too. In contrast to our study, Vallapureddy et al [ 9 ] found that sensory and motor blockades of the musculocutaneous, median, radial, and ulnar nerve distribution were similar in both groups. Choi et al [ 10 ] and Arab et al [ 11 ] found that the rate of blockage of nerves was lower in the single-point injection group, which is similar to our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Choi et al [10] and Arab et al [11] found that the rate of blockage of nerves was lower in the singlepoint injection group, which is similar to our study. [11], and Vallapureddy et al [9] all found delayed sensory and motor onset in the single-point injection group, compared to double-or triple-injection groups.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation